The Sholawat as A Form of Social Capital in The Political Contestation of Kediri Regency, Indonesia - Pipit Kiptiyah; A. Naurah Shafa Kamila (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2025)
This study examines the role of sholawat as social capital in political victory strategies in Kediri Regency, Indonesia. In every political event such as regional elections and village head elections, candidates often invite sholawat groups as part of their campaign strategies. Additionally, ahead of elections, many sholawat groups are actively involved in community activities and serve as effective tools of political communication. This phenomenon demonstrates how religious practices are used as instruments to build legitimacy and electoral support. Using a qualitative approach and Pierre Bourdieu's theory of social capital, while considering the Global South perspective, this study analyzes how sholawat forms a socially advantageous network for candidates. Religious figures and sholawat groups play a role in shaping public opinion and strengthening electability through religious symbols. This study also highlights resistance to the exploitation of religion for practical political purposes and underscores the importance of religious ethics in the political sphere. The study offers insights into the relationship between religion and politics and its relevance in Indonesia's local democracy.